Stinging Nettle (Urtica dioica L.) in Sustainable Poultry Production: Phytochemistry, Biological Activities, and Practical Applications - Teeb A. Altabtabaai; Caterin A. M. Ismail; Jamal Al-Din D. H. Jasim; Arshed H. Alhafadhi; Mohammed A. Alrubaee; Ahmed F. Alobaidi; Asawer Sharif (Health & Medical Sciences, 2026)
The present review aims to compile and critically analyze the available information on stinging nettle (Urtica dioica L.) due to its wide distribution and significant medicinal and nutritional importance. The study focuses on summarizing its botanical characteristics, phytochemical composition, and major bioactive constituents, with particular emphasis on phenolic compounds, flavonoids, saponins, tannins, and terpenes. In addition, this review highlights the potential applications of stinging nettle in poultry nutrition as a natural feed additive. It also evaluates its reported effects on growth performance, gut health, immune response, and oxidative status in poultry species, based on previously published experimental and review studies. Furthermore, the study seeks to provide a comprehensive scientific overview that supports the use of stinging nettle as a sustainable alternative to antibiotic growth promoters in modern poultry production systems. By integrating existing literature, this review aims to identify knowledge gaps and propose directions for future research regarding optimal inclusion levels, processing methods, and practical applications under commercial conditions.